2005
DOI: 10.1111/j.1523-1755.2005.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Salt loading induces redistribution of the plasmalemmal Na/K-ATPase in proximal tubule cells

Abstract: These data suggest that redistribution of the proximal tubule Na/K-ATPase in response to endogenous cardiotonic steroids plays an important role in renal adaptation to salt loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 43 publications
(49 reference statements)
3
90
1
Order By: Relevance
“…We have demonstrated that activation of this Na/K-ATPase signaling function inhibits RPT sodium reabsorption to correct sodium retention-related volume expansion and blood pressure increase. We conclude that, rather than contributing to development and maintenance of hypertension, properly regulated RPT Na/K-ATPase signaling has a protective effect under physiological settings (12,13,21,22). However, a fundamental unanswered question is the underlying mechanism to "turn on/off" the RPT Na/K-ATPase signaling.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We have demonstrated that activation of this Na/K-ATPase signaling function inhibits RPT sodium reabsorption to correct sodium retention-related volume expansion and blood pressure increase. We conclude that, rather than contributing to development and maintenance of hypertension, properly regulated RPT Na/K-ATPase signaling has a protective effect under physiological settings (12,13,21,22). However, a fundamental unanswered question is the underlying mechanism to "turn on/off" the RPT Na/K-ATPase signaling.…”
Section: Discussionmentioning
confidence: 82%
“…These include transgenic mice with a "humanized" ouabain-sensitive Na/K-ATPase ␣1 subunit, CTS infusion, and immunoneutralization of endogenous CTS (12,22,(37)(38)(39)(40). For many years, the concept of CTS elimination of excessive sodium by direct inhibition of Na/KATPase has been a topic of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Before sacrifice at 4 weeks, animals had ventricular pressures determined by placement of a 2F Millar Microtip Catheter Transducer (Millar Instruments Inc) into the left ventricle through a carotid insertion. Hemodynamic data were acquired at 500 Hz and stored electronically using a BioPac MP110 acquisition system and AcqKnowledge 4.7.3 software (BIOPAC Systems, Inc).…”
Section: Hemodynamicsmentioning
confidence: 99%
“…Recently, our group has shown that passive administration of antibodies raised against MBG reduced Na/K-ATPase endocytosis and sodium excretion in Sprague-Dawley rats given a high-salt diet. 20 On this background, we postulated that increases in circulating MBG may be in part responsible for the systemic oxidant stress state and the anatomic and functional cardiac changes seen with experimental uremia.…”
mentioning
confidence: 99%